A discussion on the new critical convergences towards the centrality of knowledge in school: the theories of the relation to knowledge of Bernard Charlot and the return of Michael Young's powerful knowledge - Adriana Marrero (Universidade Federal de Santa Catarina, 2021)
In the late 1960s, driven by the increasing capacity of computational data processing, statistics that linked school success with students' social backgrounds became the main argument in favor of the idea that schools -even the public ones- did little more than reproduce class inequalities and legitimize them by attributing school failure to the poor intellectual abilities of subordinate class students. Both in England and France, critical theories about education questioned the curriculum, which they saw as arbitrary and related to the interests and tastes of the privileged classes, as well as the authority of the teacher, transmitter of these contents and legitimizer of educative but especially social failure, of children from low strata. This apparent consensus is explicitly broken with the turn of the century, and authors such as Bernard Charlot in France and Michael FD Young in England, converge on pointing to knowledge as the central factor in educational work. The objective of this article is to examine the approaches of the two authors on this point, to compare both perspectives, and to propose overcoming visions of some distances that separate them. It concludes with a theoretical critique of both perspectives, an attempt of an overcoming synthesis, underlining the value of knowledge as a central factor in educational activities.